Parallel Quadri-valent Quantum-Inspired Gravitational Search Algorithm on a heterogeneous platform for wireless sensor networks. (June 2021) - Mirhosseini, Mina; Fazlali, Mahmood; Tabatabaee Malazi, Hadi; Izadi, Sayyed Kamyar; Nezamabadi-pour, Hossein
Abstract: Sensor nodes in a wireless sensor Network are assigned for different operational modes to perfume application-specific objectives. The decision to assign operational modes to nodes is a challenging problem in the presence of multiple criteria including energy-efficient, maintaining network connectivity, and fulfilling application goals. Several metaheuristic methods are introduced in the literature to address this NP-hard problem, however, these methods require further improvements in execution-time and finding the optimum solution. In this research, we propose an improved version of a metaheuristic method called Quadri-valent Quantum-Inspired Gravitational Search Algorithm (QQIGSA) to solve Quadri-valent problems by applying a Not Q-Gate and paralleling QQIGSA method on the graphics processing unit. The proposed method employs a heterogeneous platform and justifies its parameters. The experimental results show that the performance enhancement from 1.8 to 2.25 compared to the previous parallel implementations. Moreover, we achieve the speedup of 8 by using the proposed heterogeneous paralleling technique. Graphical abstract: Highlights: An improved Quadri-valent Quantum-Inspired Gravitational Search Algorithm is proposed. The proposed algorithm has been adopted for optimal design of wireless sensor network. The execution time is decreased using CPU–GPU heterogeneous parallelizing technique. The main parameters of the algorithms are justified. A comparison was made among the proposed QQIGSA and various other metaheuristics.